(untitled) (Journal of Laboratory Animal Science, 2024)
Fourty New Zealand white rabbits were randomly allotted to four equal dietary treatments consisting of complete mixed rations (16% CP; 15% CF) without (T0) and with 5 (T1), 15 (T2) and 25 (T3) per cent jojoba (Simmodsin chinensis) oil meal to study the toxicity as well as bone and meat characteristics. Supplementation of jojoba oil meal caused absolute mortality and the extent of mortality followed the dose response pattern. Fifty per cent of mortality rate was documented in T3 as early as 3rd week of experiment and at the end of 3rd week all experimental animals succumbed to death while no mortality recorded in control group. Chemical composition of meat and bone indicated significantly lower crude protein and ether extract contents in treated rabbits. Autopsy of rabbits which died in jojoba oil meal incorporated complete feed showed mild to severe dilated and congested mesenteric blood vessels and enlarged liver and kidney. Toxicopathological changes include hepatocellular swelling, bile duct hyperplasia, glomerular nephritis and thyroiditis indicative of simmondsin toxicity in rabbits due to jojoba oil meal.